EFEKTIFITAS KOMUNIKASI KEPALA SEKOLAH DALAM MENSOSIALISASIKAN PERATURAN-PERATURAN DI MTSN BESITANG - Nurul Aini Nurul (Jurnal Sinar Edukasi, 2021)
Principal leadership is an important force in the context of school management. Therefore, the ability to lead effectively is the main key to being a successful leader. To convey the regulations that have been set and which will be implemented, communication is needed. By using descriptive qualitative research using observation instruments, interviews and document studies, it is known that the principal's communication in disseminating the regulations at MTsN Besitang is verbal and non-verbal. Verbal communication is done orally and in writing. While non-verbal communication in the form of action. The principal as the top leadership of the school institution not only gives orders to his subordinates, but he also carries out directly as uswah for staff, teachers and students. Verbal and non-verbal communication is done using techniques such as Informative, Instructive and Human Relations. When this technique is used to achieve the effectiveness of communication carried out in disseminating the rules at school. it is known that the communication has been effective, seen from the lack of students and teachers who commit violations every year. It is known that communication plays an important role in their compliance in implementing existing regulations.